Analisis Dan Perancangan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil Dan Menengah (SAK EMKM) Pada UMKM Classyid.Thrift - Saputra, Kurniawan; Syarief, Ahmad; Rufaedah, Yanti; Supriatna, Iyeh (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This final project research was conducted at one of the Micro, Small and Medium Enterprises (MSMEs) Classyid.thrift located at Griya Mukti Asri Blok C16 no.10 RT03 RW05 Ds. Kedungdawa district. Kedawung Kab. Cirebon. This MSMEs is engaged in clothing, especially warm clothes. As long as this company is running, it has not carried out standardized bookkeeping. The standard used for MSMEs in Indonesia is the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The research method used in this research is descriptive qualitative. Data collection techniques used in this study through observation, interviews, and documentation. The results of this study will be in the form of financial statements from MSMEs Classyid.thrift based on SAK EMKM which consists of statements of financial position, income statements, and notes to financial statements.